Pemberdayaan Pemuda melalui Budi Daya Ikan Lele di Yayasan Borneo Bersinar Kalimantan Cemerlang - Defri Triadi; Stephanus Prihadi; Tiavone Theressa Andin; Eva Inriani; Yoan Colina; Cristi Devi Darnita; Petriana Petriana; Sri Renita; Tesalonika Tesalonika; Marajoko Marajoko (Jurnal Pengabdian Masyarakat (abdira), 2022)
Borneo Bersinar Kalimantan Cemerlang is a foundation that accommodates unable children from variousregions, who are given education and coaching to form character and have a  better future. In meeting daily needs, foundation funding is managed by its owners with independent business activities and expects assistance from the government and the community. Thisinitiative aims to improvethe quality of life and welfare of the foundation through the empowerment of youth in accordance with their own potential. Metode used is ABCD (Assets Based Community Development) with step 1) Field Observation, 2) Coordination With Partners, 3) Implementation of Activities, and 4) Monitoring and Evaluation of Activities. There are power and assets belonging to the foundation that can be utilized, namely unused land covering an area of 30x40m² located next to the foundation building. The land is utilized by farming catfish amounting to 7,000 fish seedlings in a pond size of 2x1x0.75m as much as 7 pieces, where later the results of catfish cultivation management will be the foundation's income.